Speech Acts Analysis Of Pride And Prejudice Novel By Jane Austen - Ridha Mardiani; Bela Sonia Leviani (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2022)
Abstract This study intends to analyze speech act used in Pride and Prejudice novel uttered by the main character. The objectives of this research are: 1) to know the most dominant type of speech act uttered by the main character found in the novel, 2) to know the contribution of the analysis to the EFL learners when learning English grammar. This research used the conversational analysis. The steps of collecting data were reading the Pride and Prejudice novel focusing on Elizabeth Bennet’s utterances in each chapter, selecting data containing speech act based on Searle’s classification, classifying the data, transferring data into a table, analyzing and interpreting the data. The result of the data analysis showed that there were only four types of speech acts; 1) 253 utterances of representatives, 2) 96 utterances of directives, 3) 4 utterances of commissives, and 4) 122 utterances of expressives. From the data can be concluded that the most dominant type is representatives speech act. We indirectly learned grammar in a way we found the speech acts from each sentence.